Kepemimpinan Kepala Sekolah Dalam Meningkatkan Mutu Akademik Siswa SD di Masa Pandemi Covid-19 - Kurnia Arumsari; Enung Hasanah (IAIN Batusangkar, 2021)
The Covid-19 pandemic has made changes in all fields, including education. Everyone in the field of education is required to do online learning. There are many obstacles in online learning, one of which is the decline of the academic quality of students. The purpose of this study is to find out the best practices of leadership implemented by the Principal of SD MuhammadiyahKarangkajen 4 Yogyakarta in improving the academic quality of students during the Covid-19 pandemic. The researchers used qualitative method and the data of the research were collectedthrough observation and interviews with school principal and the teachers. The results of this study showed that the principal opened a learning consultation service in schools. Beside the school continued implementing the health protocols recommended by the government and several requirements such as teachers and students must be in good health, not from outside the city, and no family has been affected by COVID-19. The existence of study consultations at schoolmade thestudents more enthusiastic in learning, more responsible in doing their tasks, their academic scores increase.